2019
DOI: 10.1002/biot.201800563
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Stem Cell‐Based Therapies for Type 1 Diabetes to the Clinic: Early Insights from Bioprocess Economics and Cost‐Effectiveness Analysis

Abstract: Differentiation of pluripotent stem cells (PSCs) into β cells could provide insulin independence for type 1 diabetes (T1D) patients. This approach would reduce the clinical complications that most patients managed on intensive insulin therapy (IIT) face. However, bottlenecks of PSC manufacturing and limited engraftment of encapsulated cells hinder the long‐term effectiveness of these therapies. A bioprocess decision‐support tool is combined with a disease state‐transition model to evaluate the cost‐effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
(95 reference statements)
0
11
0
Order By: Relevance
“…Emerging technologies ]such as stirred suspension bioreactor culture, wave bag bioreactor culture, multiplate culture, and roller bottle culture (32)] may eventually allow for mass production of stem cell-derived b cells and islet-like organoids. If a manufacturing expenses can be reduced, early health technology assessment studies demonstrated that stem cell-derived b-cell therapy will be a cost-effective (33,34).…”
Section: Why the Need For Stem-cell Based Therapy In Diabetes?mentioning
confidence: 99%
“…Emerging technologies ]such as stirred suspension bioreactor culture, wave bag bioreactor culture, multiplate culture, and roller bottle culture (32)] may eventually allow for mass production of stem cell-derived b cells and islet-like organoids. If a manufacturing expenses can be reduced, early health technology assessment studies demonstrated that stem cell-derived b-cell therapy will be a cost-effective (33,34).…”
Section: Why the Need For Stem-cell Based Therapy In Diabetes?mentioning
confidence: 99%
“…To achieve cost-effective manufacturing using industrial processes, synthetic small molecules are likely to replace purified proteins (Kieffer, 2016). Recent reports modeling the cost-effectiveness of hPSC-based therapy for T1D compared to intensive insulin therapy have highlighted the need for scalable manufacturing platforms for stem cell therapies (Bandeiras et al, 2019;Wallner et al, 2016).…”
Section: Cell Manufacturingmentioning
confidence: 99%
“…The encapsulation of SC-islet cells prior to transplantation allows them to detect blood glucose levels and secrete insulin while remaining isolated from the immune system of the recipient [ 101 ]. Bandeiras et al provided a cost-effectiveness analysis of encapsulated SC-islet cell transplantation that considered the cost of SC-islet cell production [ 102 ]. In their paper, the operational efficiency of the machine, labour, equipment, and reagent costs were taken into account assuming a demand of 50 patients per year, and the simulation resulted in a manufacturing cost per patient of about $80,000, which was higher than that for cadaveric islets [ 103 ].…”
Section: Cost-effectiveness Of Stem Cell-derived Islet Cells Transplantation Therapy For T1dmentioning
confidence: 99%
“…However, the cost of reagents, especially those related to the differentiation stage, will continue to be relatively large. The results of a bioprocess model, which assumed a strategy of manufacturing products for 50 patients per year and 10 patients per machine, also assumed a total final cost of $650,000 per patient for the transplantation [ 102 ]. This model estimated that, compared with IIT, SC-islet cells transplantation would increase the quality-adjusted life years (QALYs) in 96.4% of the patients by an average of 3.73 years per patient over a 20-year patient period.…”
Section: Cost-effectiveness Of Stem Cell-derived Islet Cells Transplantation Therapy For T1dmentioning
confidence: 99%